Inorganic Phosphate Modulates the Expression of the NaPi-2a Transporter in the trans-Golgi Network and the Interaction with PIST in the Proximal Tubule. (29th January 2013) - Lanaspa, Miguel A.; Caldas, Yupanqui A.; Breusegem, Sophia Y.; Andrés-Hernando, Ana; Cicerchi, Christina; Levi, Moshe; Sorribas, Victor
Abstract : Inorganic phosphate (Pi) homeostasis is maintained by the tight regulation of renal Pi excretion versus reabsorption rates that are in turn modulated by adjusting the number of Pi transporters (mainly NaPi-2a) in the proximal tubules. In response to some hormones and a high dietary Pi content, NaPi-2a is endocytosed and degraded in the lysosomes; however, we show here that some NaPi-2a molecules are targeted to the trans -Golgi network (TGN) during the endocytosis. In the TGN, NaPi-2a interacts with PIST (PDZ-domain protein interacting specifically with TC10), a TGN-resident PDZ-domain-containing protein. The extension of the interaction is proportional to the expression of NaPi-2a in the TGN, and, consistent with that, it is increased with a high Pi diet. When overexpressed in opossum kidney (OK) cells, PIST retains NaPi-2a in the TGN and inhibits Na-dependent Pi transport. Overexpression of PIST also prevents the adaptation of OK cells to a low Pi culture medium. Our data supports the view that NaPi-2a is subjected to retrograde trafficking from the plasma membrane to the TGN using one of the machineries involved in endosomal transport and explains the reported expression of NaPi-2a in the TGN.